Maternal Sensitivity Buffers the Association between SLC6A4 Methylation and Socio-Emotional Stress Response in 3-Month-Old Full Term, but not very Preterm Infants - Provenzi, Livio; Fumagalli, Monica; Giorda, Roberto; Morandi, Francesco; Sirgiovanni, Ida; Pozzoli, Uberto; Mosca, Fabio; Borgatti, Renato; Montirosso, Rosario (Frontiers in Psychiatry, 2017)
Background. Very preterm (VPT) infants are hospitalized in Neonatal Intensive Care Units (NICUs) and are exposed to life-saving procedures eliciting pain-related stress. Recent research documented that pain-related stress might result in birth-to-discharge increased methylation of serotonin transporter gene (SLC6A4) in VPT infants, leading to poorer stress regulation at 3 months of age in VPT infants compared to their full-term (FT) counterparts. Maternal sensitivity is thought to support infants’ stress response, but its role in moderating the effects of altered SLC6A4 methylation is unknown. Main aim. To assess the role of maternal sensitivity in moderating the association between altered SLC6A4 methylation and stress response in 3-month-old VPT and FT infants. Methods. 53 infants (27 VPTs, 26 FTs) and their mothers were enrolled. SLC6A4 methylation was obtained from peripheral blood samples at NICU discharge for VPT infants and from cord blood at birth for FT infants. At 3 months (age corrected for prematurity) both groups participated to the Face-to-Face Still-Face (FFSF) paradigm to measure both infants’ stress response (i.e., negative emotionality) and maternal sensitivity. Results. Maternal sensitivity did not significantly differ between VPT and FT infants’ mothers. In VPT infants, higher SLC6A4 methylation at hospital discharge associates with higher negative emotionality during the FFSF. In FT infants, SLC6A4 methylation and maternal sensitivity significantly interacted to predict stress response: a positive significant association between SLC6A4 methylation and negative emotionality emerged only in FT infants of less sensitive mothers. Discussion. Although no differences emerged in caregiving behavior in the two groups of mothers, maternal sensitivity was effective in moderating the effects of SLC6A4 methylation in FT infants, but not in VPT infants at 3 months. Speculatively, the buffering effect of maternal sensitivity observed in FT infants was disrupted by the altered early mother-infant contact due to NICU stay of the VPT group. These findings indirectly support that the effects of maternal sensitivity on infants’ socio-emotional development might be time-dependent and that mother-infant interventions in the NICU need to be provided precociously within a narrow sensitive period after VPT birth.